Effect of Pinching on Growth and Quality Flower Production of Chrysanthemum (Chrysanthemum indicum L.) - Md Ehsanullah; Shofiul Azam Tarapder; Abu Rashed Md Maukeeb; Anayat Ullah Khan; Ahasan Ullah Khan (Journal of Multidisciplinary Applied Natural Science, 2021)
A field study conceded to assess the effect of pinching on growth and quality flowers yield of chrysanthemum at Horticulture Research Centre (HRC), Gazipur, Bangladesh. The research was laid out in Randomized Complete Block Design (RCBD) with six treatments and three replications. The treatment combinations were as T0- No pinching, T1- Once 40 days, T2- Once 50 days, T3- Once 60 days, T4- Twice 40 and 50 days and T5- Thrice 40, 50 and 60 days. It was observed that the highest plant height 60cm in no pinching (T0) and the lowest 45 cm was recorded by pinching the plants thrice (T5). Days of the first flowering (57 days) was observed where no pinching was followed and significantly delay in flowering (68 days) was recorded in in pinching the plants thrice (T5). The highest number of branches (12) was recorded in pinching the plants thrice (T5) and the lowest number of branches (05) in no pinching (T0). The maximum number of leaves (235) was recorded in pinching the plants thrice (T5) and minimum number of leaves (200) was observed in no pinching (T0). The treatment T5 (pinching the plants thrice) attained maximum plant spread (30 cm) and the treatment T0 (no pinching) attained minimum plant spread (17cm). The highest number of flower (45) was recorded in pinching the plants thrice (T5) treatment and the lowest flower (28) was observed in T0 treatment. Among the six treatment, T5 (pinching the plants thrice) showed the highest efficacy and it could be used as treatment in cultivation of Chrysanthemum indicum for growth and quality flower production.